Kualitas Bakteriologis dan Higiene Sanitasi Pada Depot Air Minum Isi Ulang di Wilayah Kerja Puskesmas II Denpasar Barat - Komang Try Adnyani Rahayu; Ni Luh Utari Sumadewi; Ni Putu Widya Astuti (HIGIENE: Jurnal Kesehatan Lingkungan, 2018)
The existence of Drinking Water Refill Depot (DAMIU) continues to increase appropriate with the dynamics of community needs for drinking water that has good quality and safe for consumption. Although it had a low price, not all DAMIU product guaranteed safety. DAMIU as an alternative choice to fulfill the community needs for drinking water becomes a risk that harmful to health if producen did not pay attention in DAMIU hygiene and sanitation. The purpose of this study was to analyze quality of bacteriological and sanitation hygiene at refill drinking water depot in Puskesmas II West Denpasar. Design of this research is descriptive correlation with cross sectional method. Sampling technique of this research is non probability sampling technique that is purposive sampling with 16 sample people. Collection data using a worker's hygiene questionnaire and environmental sanitation at refill drinking water depot and Laboratory inspection instruments with MPN E. coli and MPN Coliform Parameters. Data processing using Chi Square test to determine whether or not the correlation between two variables. Results of the study were from 16 samples of 14 (87.5%) qualified in bacteriological quality and 13 (81.2%) qualified in sanitary hygiene. The concluded was a significant correlation between bacteriological quality and sanitation hygiene at refill drinking water depot in Puskesmas II West Denpasar (p value of 0.002 <0.05). From the results advisable for drinking water refill operators to always implement hygiene behavior that include clean living behavior and for Denpasar Health Department to keep performing its role in conducting guidance and supervision of sanitary hygiene problem DAMIU periodically both physical inspection and water quality.Keywords: DAMIU, Hygiene Sanitation, Quality of Bacteriological